PENINGKATAN KEMAMPUAN BERPENDAPAT MAHASISWA MELALUI PROBLEM BASED LEARNING (PBL) SEBAGAI PENDUKUNG PENCAPAIAN KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) PADA MATA KULIAH PRAGMATIK - Ahmad Syaifudin; Septina Sulistyaningrum (Jurnal Penelitian Pendidikan, 2015)
This abstract aims to explain the improvement of students’ ability in giving opinion in pragmatic subject through PBL model as a support of KKNI achievement. The research was conducted through the lesson study (LS) consisting  of the stage plan, do, and see. Results of this study revealed that there are two factors that cause low ability to express their opinions, namely anxiety (fear) and lack of ability in understanding the material concept. Through PBL models with LS system, students’ fear could be erased. It increased material concept understanding of the students. The increase was offset by an ability improvement in expressing opinions as much as 91% of the number of students involved in learning.Keywords: Problem Based Learning (PBL), KKNI